Universal Design Learning: Rehabilitation and Inclusive Education in Multidisciplinary Perspective for Inclusive Development - Anggraini, Dewi; Subasno, Yohanes (Department of Special Education, 2024)
Every person has the right to access educational services, considering that education is one of the most important elements of life in society. More specifically, education can be understood as one of the capitals used by individuals to change the order of their lives in the arena of life in various aspects. The paper aims to show the relevance of rehabilitation for persons with disabilities and inclusive education as a way to achieve inclusive development in the future through Universal Design Learning (UDL). UDL ensures the system of education should focus on the right to quality education for every child, especially those with disabilities. The exploration of the benefits of UDL is discussed through the perspectives of psychology and anthropology, sociology, and disability criticism to raise good practices and minimize the challenges that arise regarding UDL implementation. Using a systematic review in analyzing the implementation of UDL for inclusive education through grouping related articles in some countries. The results of the study concluded that UDL is an ideal concept whose implementation needs to be considered and strengthened over time to achieve inclusive development using local context.